Increasing digital capabilities of agricultural projects to reduce costs - Al-Ssadi, Nasser Jassem Nasser; Alkarawy, Heyder G Wannes; Hussein, Jassim Mohammad (Journal of Social Economics Research, 2023)
This paper provides an overview of the extent of digital transformation in the Republic of Iraq. It contains a discussion of the opportunities and challenges that the economy faces due to digitization and its potential to promote a sustainable economic transformation to achieve the 2030 Agenda for Sustainable Development. By analyzing the experience of implementing these projects, it is possible to identify the economic and accounting actions that can be taken to reduce the costs of digitizing crop production enterprises, as well as identify problems in industrial relations that impede effective digitization and the establishment of a geographic information system for regional agriculture in the Middle Euphrates, Iraq. Based on an assessment of the state of digitization in the Middle Euphrates region of Iraq, key areas for digitization efforts in the agricultural sector were identified. The study revealed the fundamental trends of modern and innovative digital technologies presented by the “Digital Agriculture” management project with special data processing methods and the use of geographic information systems that make it possible to obtain a significant economic impact to reduce and rationalize costs. According to the results obtained, the use of elements of digital technologies in crop production in the Middle Euphrates, Iraq, has a significant economic effect, the replication of which can greatly accelerate the development of the industry. These efforts to unlock Iraq’s digital potential will accelerate the achievement of the Sustainable Development Goals.